IDIOMATIC EXPRESSIONS IN ENCANTO MOVIE SCRIPT - Tasya Pyarina; Zuindra Zuindra; Emmy Erwina (Lembaga Pengembangan Kinerja Dosen, 2022)
This research aimed to investigate the meaning of idiomatic expression and to find out the types of Idiom in Encanto movie script. The researcher used McCharty and O'Dell's theory to analyze the implementation of idiomatic expression occurred in the object of this research. The qualitative research method was applied. The data were collected by watching the Encanto movie several times, determining the words, phrases, or sentences to be analyzed, and then categorizing the terms, phrases, and sentences into types of idioms based on the used theory. The result showed that there were 20 data found namely 7 Simile, 1 Binomial, 2 Proverbs, 1 Euphemism, 2 Clichés, and 6 Fixed Statement. Furthermore, this research can be a valuable information and knowledge for many people in understanding the idiomatic meaning in some media.